2013
DOI: 10.1007/s10344-013-0749-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of winter recreation on northern ungulates with focus on moose (Alces alces) and snowmobiles

Abstract: Winter recreation can displace ungulates to poor habitats, which may raise their energy expenditure and lower individual survivorship, causing population declines. Winter recreation could be benign, however, if animals habituate. Moreover, recreation creates trails. Traveling on them could reduce energy expenditure, thereby increasing ungulate survivorship and generating population benefits. Balancing recreation use with wildlife stewardship requires identifying when these effects occur. This task would be sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
(66 reference statements)
0
19
0
Order By: Relevance
“…), moose (Harris et al. ), mountain caribou ( Rangifer tarandus caribou; Seip et al. ), and wolverines ( Gulo gulo , Heinemeyer et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), moose (Harris et al. ), mountain caribou ( Rangifer tarandus caribou; Seip et al. ), and wolverines ( Gulo gulo , Heinemeyer et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, moose preferentially selected habitats away from areas of high snowmobile‐trail density (Colescott and Gillingham , Harris et al. ) and intensive snowmobile activity displaced woodland caribou ( R. tarandus caribou ) from suitable habitat (Seip et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Animal responses to human disturbance often vary depending on the type of disturbance activity. Wild reindeer fled longer distances when disturbed by skiers than snowmobiles (Reimers, Eftestøl, & Colman, ), while moose exhibited short‐term disturbance from skiers (Neumann, Ericsson, & Dettki, ) and avoidance of areas with high snowmobile trail density (Harris et al., ). Lynx did not appear to exhibit a consistent response to all dispersed recreation types, although some consistent differences between motorized and nonmotorized recreation types emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of recreationists by ungulates is well-documented (Cassirer et al 1992, Colescott and Gillingham 1998, Creel et al 2002, Neumann et al 2010, Harris et al 2014 and findings by Seip et al (2007) showed that caribou were displaced from large areas of high-quality winter habitat by snowmobiles. Displacement may result in caribou being forced into low-quality habitat and/or areas with high predation risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recreational use, both motorized and non-motorized, can negatively influence ungulate populations (Cassirer et al 1992, Colescott and Gillingham 1998, Creel et al 2002, Neumann et al 2010, Harris et al 2014. Motorized winter recreation in the form of snowmobiling can lead to range abandonment and/or increased accessibility to caribou habitat by wolves (Bergerud 1988, Seip et al 2007.…”
Section: Introductionmentioning
confidence: 99%